2007
DOI: 10.1167/iovs.06-0886
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Falls and Motor Vehicle Collisions in Glaucoma

Abstract: There is an increased risk of falls and MVCs in patients with glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
229
5
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(264 citation statements)
references
References 49 publications
6
229
5
13
Order By: Relevance
“…It has been demonstrated that the following specific conditions damage drivers both psychologically and physiologically: specific diagnoses [20] such as neurological disorders [3,21]; dementias [22]; having suffered a stroke [23]; diabetes [24]; hypoglycemia [25]; eye problems [26]; macular degeneration [27]; glaucoma [28]; sleep apnea [29]; illnesses related to motion such as rheumatoid arthritis [3,21]; and osteoarthritis [30]; and acute attacks experienced while driving [31]. Most of these disorders are controlled/studied in the systems of evaluation of drivers used in Spain and in other many countries.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the following specific conditions damage drivers both psychologically and physiologically: specific diagnoses [20] such as neurological disorders [3,21]; dementias [22]; having suffered a stroke [23]; diabetes [24]; hypoglycemia [25]; eye problems [26]; macular degeneration [27]; glaucoma [28]; sleep apnea [29]; illnesses related to motion such as rheumatoid arthritis [3,21]; and osteoarthritis [30]; and acute attacks experienced while driving [31]. Most of these disorders are controlled/studied in the systems of evaluation of drivers used in Spain and in other many countries.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study, patients with glaucoma and relatively mild field defects were shown to be over three times more likely to have fallen in the previous year, and over six times more likely to have been involved in one or more motor vehicle collisions in the previous 5 years; 52 however, no explanation was given for this association.…”
Section: Glaucoma and Fallsmentioning
confidence: 96%
“…Regarding pathological age-related changes, the risk of falling is greater in the presence of glaucoma (Haymes et al, 2007), macular degeneration (Szabo et al, 2008), and cataract (McCarty et al, 2002). It is not completely clear yet whether cataract surgery reduces this increased risk of falling (for a review, see Desapriya et al, 2010).…”
Section: Impact Of Sensory Changesmentioning
confidence: 99%